2021
DOI: 10.1007/s11469-021-00555-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social Distancing on the Mental Health of Parents and Children in Qatar

Abstract: This study investigated the effects of COVID-19-related social distancing practices on parents and children’s mental health and explored joint parent-child activities and coping strategies among Arab families in Qatar. The sample of 308 parents answered self-reported questionnaires regarding their mental health, coping strategies, activities with their children, social distancing practices, and their children’s mental health. Pearson’s correlation coefficient and structural equation modeling were carried out. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Studies found that partner support and cooperative co-parenting,13 14 20 32 and moderate physical exercise17 29 were associated with better mental health and coping among parents and caregivers during the pandemic. Lastly, some studies point towards mixed and potentially positive impacts of the COVID-19 restrictions on deepening family ties, improving couples’ relationships, and developing new family hobbies or activities 13 22 46 52–54. However, such positive benefits were typically found among parents and caregivers of older children (ie, adolescents) and families with several protective factors, including financial stability, comfortable and safe homes, enough food to eat, good health and healthy couple relationships 22 46.…”
Section: Resultsmentioning
confidence: 99%
“…Studies found that partner support and cooperative co-parenting,13 14 20 32 and moderate physical exercise17 29 were associated with better mental health and coping among parents and caregivers during the pandemic. Lastly, some studies point towards mixed and potentially positive impacts of the COVID-19 restrictions on deepening family ties, improving couples’ relationships, and developing new family hobbies or activities 13 22 46 52–54. However, such positive benefits were typically found among parents and caregivers of older children (ie, adolescents) and families with several protective factors, including financial stability, comfortable and safe homes, enough food to eat, good health and healthy couple relationships 22 46.…”
Section: Resultsmentioning
confidence: 99%
“…Also, family members can bear closer bonds while staying relatively "alone as a team" in the state of extensive quarantining. [18] To recap, social distancing as an important executive measure of limiting the spread of COVID-19 is increasingly being implemented worldwide. An optimistic foresight is that people are making an effort to minimize the loss of changing lifestyle and social productivity, aiming to reach a balance between effective disease control and relatively energetic social environment, instead of abandoning sustainability for expedient decrease of case numbers in this prolonged war against COVID-19.…”
Section: Social Distancingmentioning
confidence: 99%
“…The 19 Pakistan 20 and Saudi Arabia 21 ; 3 studies described the delayed vaccination patterns among children in Saudi Arabia, [22][23][24] while 2 studies looked into children's behavioral changes in Qatar 25 and Egypt, 26 and 2 others tackled the impact of home confinement on children's relationship with their parents in Qatar 27 and Saudi Arabia. 28 Two papers analyzed the Poliomyelitis surveillance system performance indicators as well as national immunization activities taking place in Afghanistan and Pakistan.…”
Section: Description Of the Selected Publicationsmentioning
confidence: 99%
“…28 The positive association between parental engagement in activities and enhanced mental health for children during home confinement was highlighted in a national study among parents (n=308) that took place in Qatar between June and July 2020. 27…”
Section: Journal Of Global Health Reportsmentioning
confidence: 99%
See 1 more Smart Citation